1997
DOI: 10.1002/(sici)1099-1379(199701)18:1<17::aid-job785>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Putting upward influence strategies in context

Abstract: SummaryResearchers have noted that upward in¯uence tactics are often used in varying patterns and combinations (e.g. Yukl and Falbe, 1990). This study investigated whether in¯uence strategies representing hard, soft, or rational approaches to in¯uence behavior would emerge in relation to upward in¯uence tactics of assertiveness, rationality, coalition, upward appeal, ingratiation, and exchange. Hypotheses were oered concerning the relations of selected demographic, individual dierence, relational, and opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
120
3
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 96 publications
(138 reference statements)
5
120
3
2
Order By: Relevance
“…Although based solely on US data, this typology provided initial insights into the possibility of a ''soft'' to ''hard'' hierarchy of influence that moved beyond the limits of the tactics approach. Since then, this meta-category conceptualization of influence has received substantial support (Egri, Ralston, Murray, & Nicholson, 2000;Falbe & Yukl, 1992;Farmer, Maslyn, Fedor, & Goodman, 1997;Ralston & Pearson, 2003).…”
Section: A Review Of the Subordinate Influencementioning
confidence: 99%
See 1 more Smart Citation
“…Although based solely on US data, this typology provided initial insights into the possibility of a ''soft'' to ''hard'' hierarchy of influence that moved beyond the limits of the tactics approach. Since then, this meta-category conceptualization of influence has received substantial support (Egri, Ralston, Murray, & Nicholson, 2000;Falbe & Yukl, 1992;Farmer, Maslyn, Fedor, & Goodman, 1997;Ralston & Pearson, 2003).…”
Section: A Review Of the Subordinate Influencementioning
confidence: 99%
“…Based on their 30-society study, Ralston and Pearson (2003) empirically identified a ''soft'' to ''hard'' dimensional structure, as had others (Farmer et al, 1997;Schmidt & Kipnis, 1984). However, there is an important difference between the USbased Kipnis and Schmidt (1988) influence tactic categories and the cross-culturally developed SUI dimensions (Ralston & Pearson, 2003).…”
Section: A Review Of the Subordinate Influencementioning
confidence: 99%
“…The upward influence tactics are able to affect the communication behaviors among members in intra-organization or inter-organization (Farmer et al, 1997). Moreover, there were some studies that the subordinate's assertiveness can give an unfavorable impression to his/her superior or bring about the negative effect in organizational performance (Rao et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…This scheme has been one the most used in research about influence tactics, and has been empirically and methodologically validated over the years (see [10], [11], [12], and [13]). Although the findings about frequency and use of influence tactics in presence environments are not always consistent, the data obtained from the main studies shows that the tactics that prevail in presence environments are rationality and ingratiation, followed by coalition ( [9], [11]).…”
Section: Theoretical Backgroundmentioning
confidence: 99%